2022
DOI: 10.3390/nu14102004
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Choline Supplementation Rescues Deficits in Synaptic Plasticity Following Prenatal Ethanol Exposure

Abstract: Prenatal ethanol exposure (PNEE) is a leading cause of neurodevelopmental impairments, yet treatments for individuals with PNEE are limited. Importantly, postnatal supplementation with the essential nutrient choline can attenuate some adverse effects of PNEE on cognitive development; however, the mechanisms of action for choline supplementation remain unclear. This study used an animal model to determine if choline supplementation could restore hippocampal synaptic plasticity that is normally impaired by prena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…Preclinical models have demonstrated that choline supplementation can attenuate the effects of developmental alcohol exposure, specifically alcohol-induced behavioral and cognitive alterations [ 29 , 30 , 31 , 32 , 33 , 34 ]. Moreover, choline can improve hippocampal-dependent learning and memory [ 29 , 30 , 31 , 34 ] and can enhance hippocampal plasticity [ 35 ], even when administered after developmental ethanol exposure. Recent clinical studies in FASD support preclinical findings, with cognitive improvements reported in children who received choline supplementation either prenatally [ 36 , 37 ] or postnatally [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical models have demonstrated that choline supplementation can attenuate the effects of developmental alcohol exposure, specifically alcohol-induced behavioral and cognitive alterations [ 29 , 30 , 31 , 32 , 33 , 34 ]. Moreover, choline can improve hippocampal-dependent learning and memory [ 29 , 30 , 31 , 34 ] and can enhance hippocampal plasticity [ 35 ], even when administered after developmental ethanol exposure. Recent clinical studies in FASD support preclinical findings, with cognitive improvements reported in children who received choline supplementation either prenatally [ 36 , 37 ] or postnatally [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have examined the effects of MCS on hyperexcitability, our results showing the benefits of high choline are consistent with reports that a methyl-enriched diet (including choline but also betaine, folic acid, vitamin B12, L-methionine and zinc) reduced spike wave discharges (Sarkisova et al 2023) and audiogenic seizure severity (Poletaeva et al 2014) in the offspring. Perinatal ethanol treatment that increased excitability was mitigated by choline chloride injection from postnatal day 10-30 (Grafe et al 2022).…”
Section: Benefits Of High Cholinementioning
confidence: 99%
“…Perinatal ethanol treatment that increased excitability was mitigated by choline chloride injection from postnatal day 10-30 (Grafe et al, 2022).…”
Section: Benefits Of High Cholinementioning
confidence: 99%
“…In an animal study, Sprague–Dawley rat pups received ethanol (5.25 g/kg/day) from PD 4–9 and choline chloride (100 mg/kg/day) from PD 10–30—the hippocampus collected from these rats at PD 35 or PD 60 showed choline mitigated the long tasting effect of ethanol on inflammatory tone via modulating the ratio of pro-to-anti-inflammatory cytokines [ 102 , 103 ]. In vitro electrophysiology experiments at PD 30–35 in choline-supplemented juvenile males and females from PD 10–30 showed a positive effect on hippocampal synaptic physiology that may be attributed to choline-related improvement in cognitive function [ 104 ]. Prenatal supplementation of choline (642 mg/L) in mice was found to prevent gross developmental abnormalities associated with prenatal alcohol (25%) exposure [ 105 ].…”
Section: Therapeutic Intervention Strategies For Fetal Alcohol Spectr...mentioning
confidence: 99%